My Unending Journey of Migration: An Autobiographical Inquiry - Pun, Lal Bahadur (Social Inquiry: Journal of Social Science Research, 2020)
In the journey of my life, I am moving hither and thither, which helped me to devise and construct the life stories of migration. I have echoed my real-life experience of migration, which I have attained from my childhood to till date. Academically, there is a dearth of migration research that is carried out using the autobiographical inquiry. The purpose of writing this article is to craft my stories, which I have experienced in the journey of migration. For this, I have instilled autobiographical inquiry to knit the stories, as the field of autobiographical inquiry is to imply ‘self-study’. Using an avenue of non-positivistic paradigm, I have interacted with the contexts to draw the stories of migration. Pertinently, the stories of migration are a revelation of my subjective feelings. To interpret my personal stories, I used the structuration theory from which I have explored the dialectical relationship between the system (policies, rules, and norms) and agency, that is me. Genuinely, the government and social systems, and personal decision of migration induced me to shape the stories of migration. At this age of my life, I have visited short to long distances internally and externally and lived there for a few days to some years. On other days, I do not know, where I will go and settle, it may not be in my control because I will be dependent on children and their decisions. For me, migration is an unending journey.